“Now Will Someone Kindly Tell Me What Is Her Proper Sphere?” Woman Suffrage, Women’s Political Participation, and the Populist Movement - Jean-Louis Marin-Lamellet (Transatlantica)
This article is a political and cultural history of the role of the Farmers’ Alliance and Populism in the crusade for woman suffrage in the 1880s and 1890s. Women were actively involved in the agrarian insurgency. This paper examines how Populism—more particularly Populism in the western Plains—provided women with a political space to act as civic agents without suffrage. It focuses on grassroots activists and women leaders’ mobilization, the limits electoral politics and partisanship imposed on the suffrage movement, case studies of Populist-backed state suffrage referenda, and the subversion of gender norms Populist women’s political activism represented. The article argues that Populist women’s prominent role in the male-dominated world of electioneering and their support for a radical economic agenda made woman suffrage even more transgressive in the 1890s.